Kebijakan Kepala Sekolah dalam Meningkatkan Motivasi Belajar Siswa di Sekolah Menengah Pertama 19 Batang Hari - Aldi Pratama; Dini Susilawati; Femi Amelia Qirani; Ratifa Dila Agustina; Rendy Ferdian; Tiwi Julianti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explore the role of policies implemented by the Principal in increasing student learning motivation at 19 Batang Hari Junior High School. Students' learning motivation is considered a key factor influencing their academic achievement and personal development. Using qualitative methods and a case study approach, data was collected through in-depth interviews with selected School Principals, teachers and students. The results of this research show that policies led by the Principal, such as developing motivational programs, strengthening relationships between students and teachers, and creating a conducive learning environment, play an important role in increasing student learning motivation. The implications of these findings suggest the need to develop more holistic and integrated policy strategies to increase student learning motivation in secondary education institutions. Keywords: , , , ,